Student Politics and Representation in Higher Education: A Global Perspective - Klemenčič, Manja (International Higher Education, 2024)
<h3 id="student-organizations-exist-at-most-universities-and-colleges-in-the-world-but-their-involvement-in-institutional-decision-making-varies-significantly-in-national-public-policy-making-national-student-associations-are-much-less-common-a-more-recent-development-is-strengthened-student-voice-in-education-policy-processes-in-international-organizations-and-intergovernmental-policy-processes-this-development-is-a-result-of-advocacy-of-powerful-regional-student-associations-and-their-newly-established-global-student-forum" data-pm-slice="1 1 []">Student organizations exist at most universities and colleges in the world, but their involvement in institutional decision making varies significantly. In national public policy making, national student associations are much less common. A more recent development is strengthened student voice in education policy processes in international organizations and intergovernmental policy processes. This development is a result of advocacy of powerful regional student associations, and their newly established Global Student Forum.